Street Vending: Between the Right to the City and Repression : The Case of Senegalese Workers’ Resistance in the City of Salerno - Molinero-Gerbeau, Yoan; Avallone, Gennaro (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2020)
The Senegalese street vendors of the city of Salerno have been the object, in recent years, of repressive policies resulting from the neoliberal ordering of public space that has been promoted by the institutions of this city. Through this case study, we will seek to reflect the main characteristics of the conflict, as well as the responses of the actors involved. It will thus be possible to see that, to face the repression exercised against this collective, its protagonists have reacted by deploying a notorious capacity of agency with the aim not only of resisting, but also to construct new political logics aiming to build a more democratic government of the city. Thus, the resistance of Salerno’s street vendors is part of a broader struggle, replicated in numerous other cities in the world, against “urban decorum” and for the right to the city.